Problematising mainstream Spanish antiracism: race, racism and whiteness. (2nd January 2022) - Sebastiani, Luca
ABSTRACT: In Spain, (anti-)racism is of scarce relevance to public debates and, when the topic is broached, it has mainly been discussed in relation to non-EU migration. Besides, its historical link with colonialism generally remains unacknowledged. This article analyses the problematisation of 'race' and 'racism' in this context, as performed by hegemonic stakeholders (i.e. public servants, NGOs, experts) in the fields of anti-discrimination, Roma inclusion and immigrant integration policies. As the fieldwork materials illustrate, this understanding rejects 'race' not only from a scientific-biological perspective but also as a social-political category. Accordingly, racism is depoliticised and theorised in a twofold manner: (1) as a matter of stereotypes, prejudices and lack of information about the 'Other'; (2) as the aggressive acts of explicitly racist individuals/organisations. The structural, historical and institutional dimensions of racism are addressed either as background context, or they are negated by public policies. By not confronting the uneven power relations (re)produced by racism, this approach reaffirms 'institutional whiteness' as the underlying perspective of mainstream Spanish anti-racism.